Plantain-based diet modulates atrazine-induced testicular toxicities in rats - Damilare Emmanuel Rotimi; Oluyomi Stephen Adeyemi (Asian Pacific Journal of Reproduction, 2023)
Objective: To assess the potential of plantain-based diet in modulating testicular toxicities in rats exposed to atrazine. Methods: The plantain-based diet at 50%, 25% and 12.5% were prepared from the basal diet by substituting the corn starch with plantain fruit pulp flour at different percentages. Wistar rats were fed plantain-based diet in varying concentrations ranging from 12.5% to 50% of the basal diet for 21 days before or after atrazine treatment in a two-phase experiment: preventive and therapeutic phases. The therapeutic model (n=35) had seven groups with 5 rats each, including the control, atrazine, atrazine recovery, atrazine plus plantain-based diet 50%, 25%, 12.5%, and atrazine plus quercetin groups. The preventive model (n=30) had six groups of 5 rats, consisting of the control, atrazine, 50%, 25%, 12.5% plantain-based diet plus atrazine, and quercetin plus atrazine groups. Gonadal hormones (testosterone, luteinizing hormone and follicle-stimulating hormone), sperm parameters (sperm motility, viability, morphology and concentration), and testicular function indices (protein, cholesterol, glycogen, acid phosphatase, alkaline phosphatase and lactate dehydrogenase) were measured. Results: The gonadal hormones, sperm characteristics, and testicular function indices of the rat testis decreased significantly in the atrazine group alongside degeneration of the histoarchitecture. However, plantain-based diet restored the gonadal hormone concentrations, semen parameters, and testicular function indices in both the preventive and therapeutic models. Conclusions: Treatment with plantain-based diet protects against rat testicular toxicity caused by atrazine via the modulation of gonadal hormones, sperm quality, testicular function index as well as histoarchitecture of rat testes.